2000
DOI: 10.1007/s001980070046
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Hip Axis Length and Risk of Hip Fracture in Men: Results from the Cornwall Hip Fracture Study

Abstract: Bone mineral density (BMD) and hip axis length (HAL) are important determinants of fracture risk in women. There are, however, few data concerning their predictive risk in men. The aim of this study was to determine the relationship between BMD, HAL and the risk of hip fracture in men. A case-control design was used. Cases were men aged 50 years and over with a minimal-trauma hip fracture admitted to the Royal Cornwall Hospital, Truro, during 1995-1997. Controls were recruited from a large general practice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
3
29
1
1
Order By: Relevance
“…Francis et al [3] found 56% of men with vertebral fractures to be osteoporotic at the lumbar spine (T-score 5-2.5). Pande et al [13] found 83% of men with hip fractures to be osteoporotic at the femoral neck and 36% at the lumbar spine, but the men in this study were older (mean 78.4 years compared with 60.97 years for our study).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Francis et al [3] found 56% of men with vertebral fractures to be osteoporotic at the lumbar spine (T-score 5-2.5). Pande et al [13] found 83% of men with hip fractures to be osteoporotic at the femoral neck and 36% at the lumbar spine, but the men in this study were older (mean 78.4 years compared with 60.97 years for our study).…”
Section: Discussioncontrasting
confidence: 49%
“…In men with vertebral fractures the greatest reduction in BMD was seen at the lumbar spine [3]. Similarly, the greatest reduction in BMD in men with hip fractures was seen at the femoral neck [13]. It is possible that this is the result of differential rates of loss resulting in a predisposition to particular fracture types.…”
Section: Discussionmentioning
confidence: 89%
“…7,8 This evidence, however, mainly derives from studies carried out in females, 9-13 whereas contradictory results characterize studies carried out in males. [14][15][16][17][18][19][20] Authors' opinions seem to vary widely about the ability of the neck shaft angle (NSA), one of the PFG factors, to predict osteoporotic hip fractures in males, [14][15][16]21 whereas its association with the risk of hip fracture in females 10,11,14,22 is generally accepted. Gender differences in the hip anatomy 23 have been put forward as a possible explanation for the different relationship of NSA with the hip-fracture risk between genders, whereas geographic and racial differences 24 among the examined male populations have been advocated as a possible cause of authors' discrepancies on the relationship between NSA and the hip-fracture risk in males.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Other studies have noted that HAL is linked to different types of fracture, with longer HAL linked to cervical (intra-capsular) rather than inter-trochanteric fracture [38,43]. In contrast, not all studies have found a significant association between HAL and fracture [21,44,45]. Pulkinen et al suggested that structural parameters of trabecular bone geometry predict in vitro failure loads of the proximal femur with similar accuracy as DXA, when using appropriate image analysis technology.…”
Section: Discussionmentioning
confidence: 99%